The complete chloroplast genome of a true mangrove Sonneratia apetala and its phylogenetic implications - Cui-Tian Li; Nan-Cai Pei; Yi Yin; Hai-Fei Yan; Miao-Miao Shi; Hui-Run Huang (Mitochondrial DNA. Part B. Resources, 2019)
Sonneratia apetala is a true mangrove distributed in South Asia, Southeast Asia and China. Here the whole chloroplast genome of S. apetala was assembled. The chloroplast genome was 153,052 bp in length, consisting of a large single copy (LSC) region of 87,210 bp, a small single copy (SSC) region of 18,026 bp, and two inverted repeat (IR) regions of 23,908 bp. It contained 131 genes, including 86 protein-coding genes, 37 tRNA genes and eight rRNA genes. The overall GC content was 37.3%. Phylogenetic analysis showed that S. apetala was sister to Trapa maximowiczii in Lythraceae.